Strategi Meningkatkan Pelayanan Jasa Keagenan terhadap Kapal oleh PT. Trans Shipping Agency Batam - Mada C.A Sirait; Dirhamsyah Dirhamsyah; Eka Fransiska (Logistics and Supply Chain Insights, 2026)
High-quality ship agency services are a key element in enhancing customer satisfaction and competitiveness within both national and international shipping sectors. This study aims to identify effective strategies for improving the quality of agency services at PT. Trans Shipping Agency Batam. The research methodology employed includes field research through direct observation and discussions, as well as library research using relevant books and journals as references. The findings indicate that PT. Trans Shipping Agency Batam has implemented strategies focused on service quality, managing ship owner expectations, and providing transparent evidence of service. Although operations are generally well-executed, certain obstacles persist, such as delays in the clearance in/out process caused by administrative complexity and inter-agency coordination. Recommended development strategies include enhancing human resource competencies, strengthening coordination among port authorities (Quarantine, Immigration, Customs, and Harbor Master), and optimizing information systems to monitor vessel schedules in real-time. More intensive coordination is expected to minimize operational constraints and drive service efficiency within the maritime industry.